Designing Teaching Materials for Children's Parties Clothing Based on Comics - Erni, Erni; Anggraini, Yudhistira; Rambe, Armaini; Novita, Novita; Muhibbuddin, Muhibbuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
The present study discusses the relatively low literacy skills and reading interest of students in children's fashion lectures. The learning process is not yet fully optimal because the level of understanding and psychomotor abilities of students still vary. The research purpose is to produce comic-based teaching materials for students of the Fashion Education study program to produce products that can be used by students as independent learning resources. The development model used in designing comic-based children's fashion teaching materials is the 4-D model consisting of four stages, namely 1) Define (definition), 2) Design (design), 3) Tell (development), and 4) Disseminate (dissemination). Data collection was carried out using a validation questionnaire from material and media experts. Data analysis techniques used include qualitative data analysis with descriptive methods and quantitative data analysis with validity and feasibility tests. The results of the validity test conducted by material experts produced a score of 91.5% in the very valid category. The results of the media expert validation obtained 94.46% in the very valid category. The practicality test obtained a score of 80%, included in the practical category and the effectiveness test produced a score of 80 in the Good category. Thus, it can be concluded that comic-based teaching materials are suitable for use in children's fashion learning. This product has the potential to be a source of independent learning that supports increasing literacy and reading interest in children's fashion lectures.